Strategi Pendidikan Nilai Moderasi Beragama Di Lingkungan Keluarga Berbasis Majlis Taklim Kaum Ibu Desa Sukamekar Kab. Bekasi - Hunaidah Mista; Ika Barkah; Mimi Jamilah Mahya; Galuhpritta Anisaningtyas; Abdul Nizar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to describe the extent to which mothers play a role in internalizing the values of religious moderation education as well as the efforts made by mothers in increasing insight into religious moderation in the family environment in Sukamekar village, Sukawangi district, Bekasi, West Java. The research uses qualitative a Miles and Huberman method FGD (Focus Group Discussion) approach, as well as observation, interviews, and documentation. An educational parenting seminar was held at Majlis Ta’līm of Nurul Khoir in Sukamekar village, Sukawangi, Bekasi. Pretest and post test papers were administered to obtain data from mothers in Sukamekar village regarding their knowledge and understanding of religious moderation values. Based on the results of data processing, it was concluded that there was a change in the knowledge of the Sukamekar village community, especially among mothers who initially did not understand the importance of the value of moderation in maintaining family integrity and harmony. They can better understand and able to apply it in the family environment. This would contribute to establishing a more moderate community that is at the forefront of forming families filled with tranquility (Sakinah), love (Mawaddah), and affection (Rahmah), as well as to maintaining harmony in social and national life.